2017
DOI: 10.1111/pcmr.12591
|View full text |Cite
|
Sign up to set email alerts
|

UV‐induced somatic mutations elicit a functional T cell response in the YUMMER1.7 mouse melanoma model

Abstract: Summary Human melanomas exhibit relatively high somatic mutation burden compared to other malignancies. These somatic mutations may produce neoantigens that are recognized by the immune system, leading to an anti-tumor response. By irradiating a parental mouse melanoma cell line carrying three driver mutations with UVB and expanding a single cell clone, we generated a mutagenized model that exhibits high somatic mutation burden. When inoculated at low cell numbers in immunocompetent C57BL/6J mice, YUMMER1.7 (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
195
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(218 citation statements)
references
References 26 publications
18
195
0
Order By: Relevance
“…Human melanoma has one of the highest mutational burdens of any tumor type 30 . Yet, tumors arising in most melanoma GEMMs, including our unirradiated TN and TB mice, are largely characterized by CNAs rather than SNVs 6,14,[24][25][26] . Here we find that a single UVB exposure can resolve this conundrum and effectively recapitulate the high burden of SNVs in human melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human melanoma has one of the highest mutational burdens of any tumor type 30 . Yet, tumors arising in most melanoma GEMMs, including our unirradiated TN and TB mice, are largely characterized by CNAs rather than SNVs 6,14,[24][25][26] . Here we find that a single UVB exposure can resolve this conundrum and effectively recapitulate the high burden of SNVs in human melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to human melanomas, GEMM-derived tumors are frequently characterized by a high burden of genomic copy number alterations (CNAs) and few single nucleotide variants (SNVs) 6,14,[24][25][26] . Thus, we used whole exome sequencing (WES) to determine whether a single UVA or UVB exposure would promote the formation of murine melanomas with 'humanized' cancer genomes containing a high frequency of SNVs.…”
Section: Uvb Exposure Humanizes the Genome Of Tn And Tb Melanomasmentioning
confidence: 99%
“…This strain can develop tumor immunity upon the inoculation of a small amount of human melanoma cell lines. 7 This finding suggests that T-cell response against melanocyte-specific antigens can be induced, which is relevant to the current study.…”
mentioning
confidence: 53%
“…The background of mice employed in this study is C57BL/6J, which are widely used for in vivo experiments including melanoma immunotherapy. This strain can develop tumor immunity upon the inoculation of a small amount of human melanoma cell lines . This finding suggests that T‐cell response against melanocyte‐specific antigens can be induced, which is relevant to the current study.…”
mentioning
confidence: 57%
“…Although wildtype mice rarely develop melanomas, they have been genetically engineered with oncogenic drivers to successfully provoke melanomagenesis [23][24][25][26][27] .Nevertheless, the creation of reliable melanoma models is handicapped by the inherent differences between mouse and human skin architecture and the complexity and heterogeneity of the human disease. Moreover, the majority of genetically engineered mouse (GEM) models fail to incorporate appropriate exposure to ultraviolet (UV) radiation, known to be the major etiological melanoma risk factor and speculated to enhance susceptibility to immunotherapy 28,29 , likely contributing to the low mutation burden and poor immunogenicity that characterize most models [30][31][32]33 . These differences likely compromise the relevance and validity of current preclinical mouse studies.We have reported that constitutive activation of the receptor tyrosine kinase MET in hepatocyte growth factor transgenic mice (HGF tg ) leads to the human-like localization of melanocytes within or near the epidermis, which are then susceptible to melanoma induction by a single burning dose of neonatal UV radiation 34,35 .…”
mentioning
confidence: 99%